2021
DOI: 10.1093/g3journal/jkab003
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptorftz-f1 (NR5A3)promotes egg chamber survival in theDrosophilaovary

Abstract: Gamete production in mammals and insects is controlled by cell signaling pathways that facilitate communication between germ cells and somatic cells. Nuclear receptor signaling is a key mediator of many aspects of reproduction, including gametogenesis. For example, the NR5A sub-family of nuclear receptors are essential for gonad development and sex steroid production in mammals. Despite the original identification of the NR5A sub-family in the model insect Drosophila melanogaster, it has been unclear whether D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…The expression of MnFtz-f1 in the CS of M. nipponense was significantly higher than that in the other developmental stages (Figure 7); this showed that MnFtz-f1 might play an important role in the process of oocyte mitosis. A recent study in Drosophila revealed that Drosophila oocytes could not undergo normal mitosis in the absence of Ftz-f1, suggesting that Ftz-f1 was essential for oocyte division (57). In Drosophila, Ftz-f1 is divided into two subtypes: aFtz-f1 and bFtz-f1.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MnFtz-f1 in the CS of M. nipponense was significantly higher than that in the other developmental stages (Figure 7); this showed that MnFtz-f1 might play an important role in the process of oocyte mitosis. A recent study in Drosophila revealed that Drosophila oocytes could not undergo normal mitosis in the absence of Ftz-f1, suggesting that Ftz-f1 was essential for oocyte division (57). In Drosophila, Ftz-f1 is divided into two subtypes: aFtz-f1 and bFtz-f1.…”
Section: Discussionmentioning
confidence: 99%
“…BgFtz-F1 is expressed throughout the ovary during the whole gonadotrophic cycle, and its depletion results in the complete block of oogenesis due, at least in part, to failure in the reorganization of the actin filaments of the follicle cells during choriogenesis. Interestingly, FTZ-F1 is also required for completing oogenesis in T. castaneum (Xu et al, 2010) and D. melanogaster (Beachum et al, 2021; Knapp et al, 2020). In the fly, like in B. germanica , this factor is detected throughout the ovary, and is required for follicle cells to differentiate properly into the final maturation stage (Beachum et al, 2021; Knapp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 12, 2022. ; https://doi.org/10.1101/2022.03.10.483750 doi: bioRxiv preprint completing oogenesis in T. castaneum (Xu et al, 2010) and D. melanogaster (Beachum et al, 2021;Knapp et al, 2020). In the fly, like in B. germanica, this factor is detected throughout the ovary, and is required for follicle cells to differentiate properly into the final maturation stage (Beachum et al, 2021;Knapp et al, 2020).…”
Section: Bgftz-f1 Likely Controls Embryo Segmentation and Is Required...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Drosophila has served as a classic in vivo model for use in studying aging and reproduction (23), since Drosophila reproductive biology resembles that of mammals (24,25). As compared to other animal models, Drosophila has a simple ovarian structure, short reproductive cycle, and easy gene editing (26).…”
Section: Introductionmentioning
confidence: 99%